The Effect of Share Ownership Structure to The Dividend Policy and Corporate Value of The Manufacturing Company Listed in Indonesia Stock Exchange - Muhammad Iqbal; Moch. Dzulkirom AR; Ari Darmawan (Sekolah Pascasarjana Universitas Brawijaya, 2018)
This study aims to examine the effect of share ownership structure on dividend policy and corporate value using agency theory perspective. The study involved the consumer goods industry sector of the manufacturing companies listed on IDX from 2010 to 2016. The data were analyzed by applying Smart PLS (Partial Least Square). The share ownership structure is divided into three: managerial ownership, institutional ownership and state ownership. The indicators used to measure dividend policy are Dividend per Share, Dividend Payout Ratio and Dividend Yield, while the value of the corporate is represented by MBVE, Tobin's Q and Closing Price. The structural model assessment reveals that share ownership structure has negative and significant effect to dividend policy. This means that increased managerial ownership and institutional ownership of the company will be followed by a decrease in dividend policy. The share ownership structure proved to have a positive and insignificant effect on the corporate value. This shows that the share ownership structure is not significant effect on the increase of corporate value. The dividend policy proved to have a positive and significant influence on the corporate value in the sense that the higher Dividend per Share, Dividend Payout Ratio and Dividend Yield will affect the increase of corporate value.